The Process of Recruiting and Developing Teacher’s Competency Case Study at MTs Aulia Cendekia Palembang - Yusuf, Soufran; Hartini, Titin (AT-TURATS, 2023)
This study aims to find out how the teacher recruitment process in private madrasas is carried out. This research also explores what teacher competency development has been carried out at the madrasa and what is the role of the madrasa head in developing teacher competence. This research was conducted at MTs Aulia Cendekia Palembang. The research method used is a qualitative method. The results of the study revealed that the teacher recruitment process had been carried out in accordance with applicable regulations. Teacher competency development is carried out by providing training to teachers, providing financial assistance to continue their education to higher educational levels, facilitating teachers to get scholarships from universities and actively encouraging teachers to take part in the PPG selection and MGMP forum. It also explains how the role of the head of the madrasa in developing teacher competence. This research has implications for the madrasah, especially the head of MTs Aulia Cendekia to more fully encourage teachers to make scientific publications. It is intended that teacher competencies related to scientific tradition and culture can be well developed.